The portability of social benefits across borders - Robert Holzmann (IZA World of Labor, 2018)
The importance of benefit portability is increasing in line with the growing number of migrants wishing to bring acquired social rights from their host country back to their country of residence. Failing to enable such portability risks impeding international labor mobility or jeopardizing individuals' ability to manage risk across their life cycle. Various instruments may establish portability. But which instrument works best and under what circumstances is not yet well-explored.
Keywords: J65; J41; J33; J08; 330; labor mobility; social risk management; bilateral social security agreements; individual and fiscal equity; bureaucratic efficiency